2012
DOI: 10.3866/pku.whxb201203021
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Study of H<sub>2</sub> Dissociative Adsorption Reactions on WO<sub>3</sub> Surfaces

Abstract: The reaction mechanism of H2 dissociative adsorption on WO3 surfaces was studied by a first-principles method. Calculations for the clean surface indicated that the c(2×2) reconstruction was the most stable surface geometry. Four H2 dissociative adsorption models were investigated. The optimal configuration was for two H atoms adsorbed at the terminal O1c site, followed by water formation and an oxygen vacancy on the surface. The density of states (DOS) results revealed that H2 dissociative adsorption led to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…Our calculated results of adsorption energies are denoted in tables 2 and 3. It is found that a part of adsorption energies are negative, which suggests that CH 4 molecule is adsorbed at the adsorption site 3.83 0.40 Tian et al [73] 3.82 0.59 1 has a free bond and is also the outermost atom, this result is reasonable and also suggested by other calculations related with WO 3 surfaces [78,79].…”
Section: Bulk Propertiessupporting
confidence: 69%
See 1 more Smart Citation
“…Our calculated results of adsorption energies are denoted in tables 2 and 3. It is found that a part of adsorption energies are negative, which suggests that CH 4 molecule is adsorbed at the adsorption site 3.83 0.40 Tian et al [73] 3.82 0.59 1 has a free bond and is also the outermost atom, this result is reasonable and also suggested by other calculations related with WO 3 surfaces [78,79].…”
Section: Bulk Propertiessupporting
confidence: 69%
“…where E slab (W n O 3n ) is the total energy of the slab, E bulk (WO 3 ) is the total energy of cubic WO 3 unit cell, n is the number of W atoms in the supercell, and S is the surface area of WO 3 (001). The results of the research [73] show that the c(2×2) reconstruction is energetically the most favorable with the lowest surface energy, and the WO 3 (001) surface is the most stable surface, which is in good agreement with that obtained from experimental low-energy electron diffraction and scanning tunneling microscope studies of the WO 3 (001) surface [62]. In order to better discuss the effect of Au atom doping on WO 3 adsorption performance, we choose two doping sites as comparison.…”
Section: Bulk Propertiesmentioning
confidence: 99%
“…Therefore, the current study intends to choose HDR as a probe reaction to evaluate the influence of first-row transition metals supported on world’s smallest cage C 20 fullerenes as SACs and their catalytic performance. Nowadays, quantum chemical-based density functional theory (DFT) simulations are considered as the highly effective approach to evaluate the nature of a catalyst and corresponding catalytic efficiency. Hence, the density functional theory calculation method is adopted to systematically probe the hydrogen dissociation on transition metal (M = Sc–Zn)-doped C 20 fullerenes as SACs to elucidate the catalytic performance of designed catalysts. Furthermore, the designed catalysts are investigated for stability, improved hydrogen adsorption capacity, and their catalytic activity for hydrogen dissociation reaction.…”
Section: Introductionmentioning
confidence: 99%